ANALISIS DESKRIPSI HASIL BELAJAR MATA KULIAH PENGANTAR TEOLOGI PADA MAHASISWA PENDIDIKAN KEAGAMAAN KATOLIK ANGKATAN 2021 - Sinaga, Rotua Dominika (Pastoralia Jurnal Penelitian Dosen, 2024)
This research aims to provide an overview of student learning outcomes in the Introduction to Theology course. Student learning outcomes in the Introduction to Theology course are relatively low. The researcher estimates that the average score for introductory theology learning outcomes for students in the class of 2021 is the same as the population score of 65. The sample in this study was 30 STPK St. John Rasul Jayapura students in the Catholic Religious Education Study Program class of 2021. The method used was quantitative descriptive analysis. The samples tested in this study included independent samples or unpaired samples. The data used is in the form of documents on learning outcomes for the Introduction to Theology course from 30 students from the class of 2021. Data collection techniques are through participatory observation and unstructured interviews with students. To answer the hypothesis, this research was carried out using the One Sample t Test. Based on the results of the One Sample t Test, it was found that the Sig (two-tailed) value was 0.020≤0.05, thus HO was rejected in this study, meaning that the learning outcomes score for the introductory Theology course for the class of 2021 students was not the same as 65, even the average score The average student class of 2021 is still less than the average population score of -1.42. The learning outcomes scores for Introduction to Theology for students from the class of 2021 are still far from the average scores for the population.